2014
DOI: 10.1002/iub.1310
|View full text |Cite
|
Sign up to set email alerts
|

The strength of aversive and appetitive associations and maladaptive behaviors

Abstract: Certain maladaptive behaviors are thought to be acquired through classical Pavlovian conditioning. Exaggerated fear response, which can develop through Pavlovian conditioning, is associated with acquired anxiety disorders such as posttraumatic stress disorders (PTSD). Inflated reward-seeking behavior, which develops through Pavlovian conditioning, underlie some types of addictive behavior (e.g., addiction to drugs, food, gambling). These maladaptive behaviors are dependent on associative learning and the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 102 publications
0
11
0
Order By: Relevance
“…Beyond hemispatial learning, the present results may also have clinical implications. Specifically, some individuals are at higher risk of developing mental disorders (Chambers et al, 2004;Indovina et al, 2011), and recent evidence links the development and maintenance of mental disorders to biased learning processes (Itzhak et al, 2014;Mineka and Oehlberg, 2008). Therefore, studying individual differences in the neural mechanisms underlying learning may be relevant for understanding why some individuals may be more likely than others to develop mental disorders.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond hemispatial learning, the present results may also have clinical implications. Specifically, some individuals are at higher risk of developing mental disorders (Chambers et al, 2004;Indovina et al, 2011), and recent evidence links the development and maintenance of mental disorders to biased learning processes (Itzhak et al, 2014;Mineka and Oehlberg, 2008). Therefore, studying individual differences in the neural mechanisms underlying learning may be relevant for understanding why some individuals may be more likely than others to develop mental disorders.…”
Section: Resultsmentioning
confidence: 99%
“…We also demonstrated that even in DSI counterconditioned mice, a subsequent cocaine history that is long enough (i.e., four 15 min cocaine conditioning sessions) is sufficient to overcome the protective effect of DSI. Our findings also suggest that both the reversal of CPP from cocaine to DSI as well as that from DSI to cocaine, i.e., counterconditioning in either case, requires a learning process spanning four conditioning sessions (and not only a single one), regardless of the nature (i.e., cocaine as a prototypical drug of abuse vs. DSI as a physiologic stimulus) or the attractiveness of the initial stimulus (for critical evaluations of stimulus strength in various CPP procedures see e.g., Bardo et al, 1995 , 2013 ; Bardo and Bevins, 2000 ; Tzschentke, 2007 ; Itzhak et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the cocaine-induced CPP model, appetitive context is associated with drug reward effect, which will elicit a conditioned response after conditioning. The conditioned response is strongly dependent on the strength of the LTM of the association between appetitive context and drug effect ( Itzhak et al, 2014 ). Cocaine self-administration is also dependent on reinforcement learning, whereas an operant behavior is involved in this process, which makes it completely different from the CPP behavior ( Aguilar et al, 2009 ; Sorg, 2012 ).…”
Section: Discussionmentioning
confidence: 99%